STUDENTS' GRAMMATICAL PROBLEMS IN ENGLISH PASSIVIZATION: What to Do for Having Better Learning on EFL Grammar at University? - Jufrizal Jufrizal (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Most EFL learners in Indonesia have local languages as their native languages (L1) with different grammatical features and properties. Such linguistic condition causes different problems on learning English at any levels in Indonesia. In addition to L1 interference. students'problems on having better grammatical competence in the foreign language are caused by problematic learning materials, methods and techniques of learning. Many students of English Department were in serious problems in writing passive voice and related constructions as found in their academic writings. It was also found that some students did not know the nature of English passivization and did silly mistakes in writing passives and medio-passives. This paper, which is derived and further developed based on research results conducted in 2012, discusses: (i) the types and causes of students' grammatical problems in English passivization; and (ii) how the English grammar instruction at university level should be belter shaped in order that the students'grammatical problems can be academically overcome. The data presented in this paper are those collected based on library research conducted in 2012 and additional one coUected when reading texts written by E,nglish Department students of Universitas Negeri Padang. The analyses and discussion are based on the theories on grammatical typology of English passivization and leaming principles of foreign language learning related to linguistic-grammatical competency.